How European consumers value wine credence attributes: a cross-country comparison of France, Greece and Italy - Raffaele Zanchini; Simone Blanc; Stefanos Theodorakis; Giuseppe Di Vita; Valentina Maria Merlino; Filippo Brun; Stefano Massaglia (Wine Economics and Policy, 2024)
Several attributes can be used to differentiate wine products to meet consumer interest and thus increase producer visibility, attractiveness and revenues. Perception of the same attribute may depend on various factors that characterise the subjects, such as individual, behavioural and situational characteristics, like their country of origin. This study aims to identify which credence attributes and related levels motivate consumers the most to buying wine, by comparing the results obtained in three different European countries: France, Greece and Italy. A conjoint experiment based on linear assumption was administered using price, production method, Geographical Indications (GIs) and wine origin as product attributes. The conjoint data were analysed in three steps: performing a model with the whole sample; performing three models using national data to compare results between the countries; and performing a cluster analysis using the Ward method to associate consumer characteristics with product attributes. Results show that wine origin is the most valued attribute for choosing wine, followed by the production method. Cross-country evaluation reveals several significant differences among the attributes of the production method, geographical indication and origin. The cluster analysis identified three groups named: Higher-priced and nation-specific wine seekers; Certification seekers and Price-sensitive consumers. This paper provides several implications for both academicians and enterprises. Indeed, it is the first evaluation comparing the role given by consumers to biodynamic certification in a cross-country evaluation. Several indications are also provided for producers who can help differentiate better wine production by earning a higher income.